(untitled) (Bangladesh Journal of Urology, 2025)
One of the top listed urological problem wrongly diagnosed and treated is bladder pain syndrome (BPS)or interstitial cystitis(IC) . Most of us diagnose it as repeat bladder infections may have taken antibiotics over and over again with little or no relief. It is mistakenly treated also as over active bladder. Interstitial cystitis is diagnosed clinically on the basis of high suspicion of a clinician. There are multiple definitions of interstitial cystitis in national and international guidelines, the international continent society (ICS) prefers the term "painful bladder syndrome" defined as the complaint of suprapubic pain related to bladder filling accompanied by increased frequency in absence of proven urinary infection or other obvious pathology [1 ] .The society(ICS) reserves the diagnosis of interstitial cystitis for patients with typical cystoscopic and histological features. This definition miss about one third of the patients primarily because it confines the pain to a suprapubic location only in bladder filling[2]. Recent survey based studies found IC/ BPS prevalent in 1.9 - 4.2% of adult men[3 ] and 2.7 - 6.5% of adult women [4] . Early in 20th century Guy Hunner reported on women with a history of suprapubic pain ,frequency ,nocturia and urgency lasting an average of 17 years. He drew attention to the disease and the red, bleeding areas he described on the bladder came to be called Hunner ulcers. But in next half century urologist would look for ulcers and failed to make the diagnosis in their absence. In 1949 Hand first noted discrete submucal patechial hemorrhage turnmed as glomerulations which is considered as an important feature of IC. He portrayed three grades of the disease, 69% of patient has grade 1 disease and only 13% has grade 3 i.e small capacity scarred bladder. Bangladesh J. Urol. 2024; 27(2): 143-145